Hubungan Tingkat Stres Dan Aktivitas Fisik Dengan Kualitas Tidur Mahasiswa Diploma Tiga Keperawatan Stikes Panti Rapih Yogyakarta - Nugraheni, Hilaria Asri; Setya Widyastuti , Chatarina; Maura Hardjanti , Sr. Therese (I Care Jurnal Keperawatan STIKes Panti Rapih, 2022)
Background: Final-level students have various academic assignments that must be accomplished on time. This condition leads to the increasing physical activities and stress. Furthermore, it has impact on the sleep quality. Objective:The study aim stoidentify the relationship of stress levels and physical activity with the sleep quality of final-level students of the Diploma Three Nursing Study Program of STIKes Panti Rapih Yogyakarta. Methods: The research method used is a correlative analytical prescription with a cross sectional design. The population in this study is all students of the final level of The Diploma of Three Nursing Program STIKes Panti Rapih Yogyakarta. Then, sampling by a total side method as many as 95 students. In the data retrieval of stress levels using the Perceived Stress Scale-10 (PSS-10) instrument, physical activity with the International Physical Activity Questionnaire-Short Form (IPAQ-SF), and sleep quality with the Sleep Quality Questionnaire (KKT). Results: Low stress levels were 1 (1.1%), moderate stress 63 (66.3%), and severe stress 31 (32.6%). Furthermore, moderate activity data amounted to 38 (40.0%) and high activity 57 (60.0%). The data indicated that bad sleep quality as much as 93 (97.9%) and good sleep quality 2 (2.1%). Spearman Rho's analysis showed a link between stress levels and sleep quality (r=-0.530, p= 0.000) and a relationship between physical activity and sleep quality (r= -0.347, p= 0.001). Conclusion:There is a relationship between stress levels and physical activity and sleep quality of the students at the final level of the Third Diploma of Nursing Study Program STIKes Panti Rapih Yogyakarta. It is expected that students are able to have stress management and maintain their physical activity in order to have good sleep quality. Moreover, educational institutions can also do health promotion for the students.